Writing Anxiety of Indonesian EFL Learners: Possible Causes and Coping Strategies - Inggarwati, Devanda Diah; Tasnim, Zakiyah; Setyono, Budi (English Education Study Program, 2022)
Abstract The objectives of this research were to find the causes of Indonesian EFL learners’ writing anxiety and how they cope with writing anxiety at one of the state junior high schools located in the rural area of Banyuwangi. In this study, the researcher employed a qualitative approach by conducting semi-structured interviews with the five participants who potential experienced in writing anxiety. The findings of this study revealed that the causes of writing anxiety were internal cause, external causes, and linguistic causes. The internal causes include psychological sources. External causes include: (1) classroom practices and (2) interpersonal threats. While, lingusictic cause include writing aspects. In addition, the strategies that the Indonesian EFL learners use to cope with writing anxiety was categorized into a theme named strategies to cope writing anxiety.